Comparative analysis of a 3D printed polymer bonded magnet composed of a TPU-PA12 matrix and Nd-Fe-B atomised powder and melt spun flakes respectively - Granit Hajra; Mihael Brunčko; Leo Gusel; Ivan Anžel (Journal of Materials Research and Technology)
The present study reports the development of new polymer bonded magnet containing a Thermoplastic Polyurethane (TPU) – Nylon (PA12) blend as the matrix material and Nd-Fe-B magnetic particles. Two composite materials were explored: one using Nd-Fe-B atomised spherical powder (ASP) and another incorporating Nd-Fe-B melt-spun flakes (MSF). The filaments were formulated by blending TPU, PA12, and one of selected type of Nd-Fe-B particles using a mixing device. The ASP and the MSF were integrated into the matrix via a precise compounding process and 3D printing was used to produce the testing specimens. The preliminary findings indicate that both formulations exhibited promising magnetic properties while maintaining the mechanical characteristics of TPU and PA12. The atomised spherical powder formulation demonstrated worse magnetic behaviour compared to the melt-spun flake formulation. ASP particles enable better fluidity of the composite material during 3D printing. However, the close-packed arrangement of these particles is the cause of much higher porosity and consequently the poorer mechanical and magnetic properties. Optimization of the processing parameters showed significant influence on the final magnetic performance and structural integrity of the printed specimens.